The creation of Beethoven's 35 piano sonatas - Cooper, Barry (Barry A. R.) (Abingdon, Oxon ; New York, NY Routledge, 2017)
Beethoven's piano sonatas are a cornerstone of the piano repertoire and favourites of both the concert hall and recording studio. The sonatas have been the subject of much scholarship, but no single study gives an adequate account of the processes by which these sonatas were composed and published. With source materials such as sketches and correspondence increasingly available, the time is ripe for a close study of the history of these works. Barry Cooper, who in 2007 produced a new edition of all 35 sonatas, including three that are often overlooked, examines each sonata in turn, addressing questions such as: Why were they written? Why did they turn out as they did? How did they come into being and how did they reach their final form? Drawing on the composer's sketches, autograph scores and early printed editions, as well as contextual material such as correspondence, Cooper explores the links between the notes and symbols found in the musical texts of the sonatas, and the environment that brought them about. The result is a biography not of the composer, but of the works themselves.--Publisher
Approaching Beethoven's piano sonatas -- The Bonn sonatas -- The Opus 2 sonatas and Haydn -- The sonatas of 1796-97 -- The sonatas of 1798-1800 -- New century, new approaches -- A 'new path'? -- The middle period opens up -- A Clementi commission -- Moving into the late period -- The last three sonatas.
Includes bibliographical references (pages 207-214) and index.
Keywords: Beethoven, Ludwig van -- 1770-1827.; Sonatas (Piano) -- History and criticism